233k views
5 votes
Can anyone help me to solve this?

Can anyone help me to solve this?-example-1

1 Answer

3 votes

Answer:

f(1/x) = (7x+3)/(2x+6)

g(x-2) = √(x² -13x +22)

Explanation:

Given equations for f(x) and g(x), you want to find simplified equations for f(1/x) and g(x-2).

F(1/x)

Substituting the argument for the variable, we have ...


f\left((1)/(x)\right)=(3\cdot(1)/(x)+7)/(6\cdot(1)/(x)+2)\\\\\boxed{f\left((1)/(x)\right)=(7x+3)/(2x+6)}

G(x-2)

Substituting the argument for the variable, we have ...


g(x-2)=√((x-2)^2-9(x-2))=√(x^2-4x+4-9x+18)\\\\\boxed{g(x-2)=√(x^2-13x+22)}

User Maryjane
by
5.5k points